Synthesis, Characterization and Comparison of Novel Poly (sebacic anhydride) Biopolymeric Implants and Microspheres for the Controlled Release of an Anticancer Drug - Kala, Shabari Girinath; Chinni, Santhivardhan (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The purpose of this study was to investigate the comparative drug release kinetics of implants and microspheres of an anticancer drug loaded onto a bio-degradable polymer. Methods: Poly (sebacic anhydride) was synthesized using a melt-polycondensation reaction, and its physicochemical properties were determined using gel permeation chromatography, nuclear magnetic resonance, differential scanning calorimetry, and Fourier transform infrared techniques. The polymer was used to encapsulate drugs via the melt moulding technique for implants and the solvent evaporation technique for microspheres. Results: In-vitro degradation of implants showed a 95% degradation rate in 6 days with the disappearance of the anhydride peak due to polymer hydrolysis. The microspheres of size 63 ± 3 μm were found to be spherical and porous in optical microscopy images. In-vitro drug release from implants (85 ± 3.5%) and microspheres (88 ± 4.5%) in pH 7.4 revealed similar sustained drug release following Higuchi kinetics. Conclusion: There was no significant difference observed in drug release patterns from implants and microspheres with the same quantity of polymer. Therefore, poly (sebacic anhydride) could become a successful candidate for controlling the release of a drug over a long period of time.
Keywords: Implants; Microspheres; Drug delivery; Sustained release; Biodegradation